Validation of the 33-Item Hypomania Checklist-External Assessment in Screening Adolescents for Bipolar Disorder - Chen, Xu; Cai, Hong; Bai, Wei; Sha, Sha; Cheung, Teris; Ungvari, Gabor S.; Feng, Yuan; Xiang, Yu-Tao; Angst, Jules (Frontiers in Psychiatry, 2022)
Bipolar disorder (BD) is often associated with misdiagnosis, leading to poor treatment outcomes. Thus, accurate assessment of BD is of great importance, including in BD adolescents. The aim of the study was to explore the psychometric properties of the 33-item Hypomania Checklist-external assessment (HCL-33-EA) in depressed adolescents. The study was conducted between March and November 2020. Depressed adolescents aged between 13 and 17 years, diagnosed with BD or major depressive disorder (MDD), according to the International Classification of Diseases, Tenth Revision (ICD-10) were recruited. Patients’ hypomanic symptoms were assessed by their carers using the HCL-33-EA. A total of 260 patients were recruited to the study, 113 of whom were diagnosed with MDD and 147 with BD. The HCL-33-EA showed high internal consistency (Cronbach’s alpha = 0.82) with two factorial dimensions. The Receiver Operating Characteristic (ROC) curve analysis revealed an area under the ROC curve (AUC) value of 0.61 (95% confidence interval (CI): 0.54-0.67). The optimal cut-off score of 7 generated the best combination of sensitivity (0.81) and specificity (0.37) for discriminating between adolescents with BD and MDD. The HCL-33-EA, with a two-factor structure, seems to be a useful tool for screening for BD in depressed adolescents. However, the high sensitivity and low specificity of the HCL-33-EA at the optimal cut-off value of 7 indicate that the HCL-33-EA needs to be modified and further refined for young patients.